A Short Overview of Biological Fuel Cells - Ivan Vito Ferrari; Luca Pasquini; Riccardo Narducci; Emanuela Sgreccia; Maria Luisa Di Vona; Philippe Knauth (Membranes, 2022)
This short review summarizes the improvements on biological fuel cells (BioFCs) with or without ionomer separation membrane. After a general introduction about the main challenges of modern energy management, BioFCs are presented including microbial fuel cells (MFCs) and enzymatic fuel cells (EFCs). The benefits of BioFCs include the capability to derive energy from waste-water and organic matter, the possibility to use bacteria or enzymes to replace expensive catalysts such as platinum, the high selectivity of the electrode reactions that allow working with less complicated systems, without the need for high purification, and the lower environmental impact. In comparison with classical FCs and given their lower electrochemical performances, BioFCs have, up to now, only found niche applications with low power needs, but they could become a green solution in the perspective of sustainable development and the circular economy. Ion exchange membranes for utilization in BioFCs are discussed in the final section of the review: they include perfluorinated proton exchange membranes but also aromatic polymers grafted with proton or anion exchange groups.